(untitled) (International Journal of Engineering and Computer Science, 2017)
FPGA (Field Programmable gate Array) devices are one of the modern technologies that are changing the electronic industry. They are riding the same integrated circuit process curves as processors and memories and keep getting larger, faster, and cheaper and are now common in low and mid volume embedded products With the advances of FPGA technology, many engineers now have the opportunity to do medium scale digital design. They can be found in primary and secondary surveillance radar, satellite communication, automotive, manufacturing, and many other types of products. Time triggered communication within FPGA is enhanced with the help of UART (Universal Asynchronous Receiver Transmitter).It translates between serial and parallel bits of data. The device changes incoming parallel information to serial data which can be sent on a communication line. A second UART can be used to receive the information. The UART performs all the tasks, timing, parity checking, etc. needed for the communication. UART is designed in VHDL. The design process involves converting the requirements into a format that represents the desired digital function(s).